2013
DOI: 10.1093/cid/cit197
|View full text |Cite
|
Sign up to set email alerts
|

Incident Hepatitis C Virus Infection in Men Who Have Sex With Men: A Prospective Cohort Analysis, 1984-2011

Abstract: The spread of HCV among both HIV-infected and -uninfected MSM in the United States has been ongoing since the beginning of the HIV epidemic. In HIV-infected men with <500 CD4(+) T cells, the HCV incidence rate was inversely proportional to CD4 T-cell count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 22 publications
8
109
2
2
Order By: Relevance
“…[34][35][36][37][38] Similar to crosssectional studies, CAI 32,37,39 and a history of syphilis 32,37 were also reported as risk factors for incident HCV infection. However, the association with CAI was only significant in non-IDU in one Swiss clinic-based study of 1543 HIV-positive men.…”
Section: Other Risk Factors In Addition To Injecting Drug Usementioning
confidence: 57%
See 1 more Smart Citation
“…[34][35][36][37][38] Similar to crosssectional studies, CAI 32,37,39 and a history of syphilis 32,37 were also reported as risk factors for incident HCV infection. However, the association with CAI was only significant in non-IDU in one Swiss clinic-based study of 1543 HIV-positive men.…”
Section: Other Risk Factors In Addition To Injecting Drug Usementioning
confidence: 57%
“…31 The large-scale Multicenter AIDS Cohort in the US reported an HCV incidence of 1.6 per 1000 person-years in non-IDUs, and this was significantly higher in previous and current IDUs (6.9 and 25.8 per 1000 person-years, respectively). 32 In Melbourne, Australia, 620 HIV-positive men were followed up for a total of 4359 person-years, and the incidence of HCV was significantly higher in IDUs (hazard ratio = 8.7, 95% CI 4.6-16.6). 33 …”
Section: Injecting Drug Use As a Risk Factormentioning
confidence: 99%
“…A prospective US cohort study demonstrated an association of incident HCV with higher numbers of receptive unprotected anal intercourse partners, as well as injecting drug use and HIVpositive status. HCV incidence was 0.5 per 1000 PY in HIV-negative MSM compared to 4.2 per 1000 PY in HIV-positive MSM (171). In a systematic review of 38 cross-sectional studies, the pooled HCV prevalence was found to be significantly higher in HIV-positive men (8.3%, 95% CI: 6.7-9.9) than in HIVnegative men (1.5%, 95% CI 0.8-2.1).…”
Section: Hepatitis Cmentioning
confidence: 88%
“…Nonetheless, HCV incidence was only 0.5 per 1000 PY in HIV-negative MSM compared with 4.2 per 1000 PY in HIV-positive MSM. 105 Among HIVpositive MSM in Australia and overseas, there are recent data supporting sexual or permucosal HCV transmission. 101,106,107 In a recent Australian study, 60% of HIV-positive Australian MSM with acute HCV did not report an IDU history.…”
Section: Hepatitis C Virusmentioning
confidence: 99%